Interactions between reflection and praxis in the history of economic thought : the case of the franciscan circles from XIII century Assisi to the present - Parisi, Daniela (2011)
Fil: Parisi, Daniela. Pontificia Universidad Católica Argentina. Departamento de Economía de la Facultad de Ciencias Sociales y Económicas; Argentina